Innovation as socially shared practice: the contribution of the Teaching and Learning Center - Fabbri Loretta; Rossi Pier Giuseppe; Giannandrea Lorella; Romano Alessandra (Research on Education and Media, 2023)
The contribution describes a study on the organizational devices and the professional development programs carried out at the Teaching and Learning Center (TLC) of the University of Siena and at the Teaching and Learning Lab (TLL) of the University of Macerata. The focus is on systemic actions capable to elicit innovation at an organizational level, starting from the work of the institutional centers for research, professional training, and digital enhanced learning embedded in the university. In the final paragraph, future developmental trajectories for constituting an inter-universities network of TLCs are discussed.